A retrospective cohort study: do patients with graves’ disease need to be euthyroid prior to surgery? - Abrar Al Jassim; Tim Wallace; Sarah Bouhabel; Agnieszka Majdan; Michael Hier; Veronique-Isabelle Forest; Richard Payne (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The 2016 American Thyroid Association guidelines indicate that patients with Graves’ disease who undergo a thyroidectomy should be rendered euthyroid through the use of antithyroid drugs (ATD) prior to surgery to avoid complications such as a thyroid storm. At times, the use of ATDs can have limited efficacy and therefore some patients will inevitably remain biochemically hyperthyroid at the time of surgery. The aim of this study is to assess if hyperthyroid patients undergoing a thyroidectomy are at an increased risk of developing a thyroid storm in comparison to euthyroid patients. Furthermore, this study seeks to establish a correlation between thyroid storm identified by the levels of thyroid hormones (T3 and T4) and the level of thyroid stimulating hormone (TSH). Methods A retrospective cohort study was conducted at two Canadian centers, one in Montreal and the other in Nova Scotia. Sixty-seven patients undergoing thyroidectomy for Graves’ disease from January 2006 to December 2016 were evaluated. Results The study comprised 67 participants with a mean age of 46 years (range16–78 years). A total of 78% of patients were on methimazole, 34% on beta-blockers, 27% on potassium iodine solution, 10% on propylthiouracil and 7% on steroids. At the time of surgery 21% were in an overt hyperthyroid state and 33% were in a subclinical hyperthyroid state. The average TSH level of 0.03 mIUL/L (range 0.01–0.23 mIUL/L). Sixteen percent of patients had a TSH level less than 0.01 mIUL/L. The average free T4 level was 29.58 pmol/L (range 11.5–95.2 pmol/L). The average total T3 level was 11.52 nmol/L (range 4.5–29.1 nmol/L) and free T3 level was 6.35 pmol/L (range 6.1–6.6 pmol/L). No patient developed thyroid storm. Conclusions In our study, biochemically hyperthyroid patients undergoing thyroidectomy did not develop thyroid storm. Additional studies with larger sample sizes are needed to better understand the risk of thyroid storm in hyperthyroid patients.